Research on Failure Precursor Based on Characteristics of Energy Dissipation Rate for Rock - Liu, Xiaohui; Xue, Yang; Zheng, Yu; Li, Hongying (Frontiers in Earth Science, 2022)
Research on early warning of rock disaster has a positive influence on safety and stability of underground engineering. Predicting rock failure precursor based on energy theory is closer to the essence of rock failure to analyze instability mechanism of engineering surrounding rock. Based on this, static compression tests and acoustic emission (AE) tests of coal rock under 0,8,16 and 25MPa confining pressures were carried out on MTS815 test system. According to the relationship between mechanical parameters, AE parameters and energy dissipation rate (EDR) in rock failure process, energy evolution law of rock failure was analyzed, and a new index for evaluating rock failure precursory was proposed based on EDR. The results show that the EDR has a good correlation with mechanical strength and AE events under different confining pressures, and EDR can truly characterize deformation and failure characteristics of coal rock. Confining pressure can obviously enhance the EDR level in pre-peak. When EDR reaches the peak, AE events increase rapidly. In post-peak stage, the EDR peak value is concentrated and large, AE event is highly active and stress drops abruptly, indicating that the EDR is reliable for evaluating rock failure process. Comparing with AE test results, it is found that the warning stress and warning time of EDR failure precursor is later than that of AE failure precursor, the former is closer to the peak stress of rock. EDR failure precursor is more universal in engineering, and could provide better reference value for preventing rock disaster.